Plantar calcaneal tumor as a differential diagnosis of plantar fasciitis: A case report (Research, Society and Development, 2025)
Plantar fasciitis is a common orthopedic complaint, especially among athletes, obese individuals, and people over 40 years old. Despite its prevalence, it is crucial to explore other potential causes of similar symptoms. The hindfoot, particularly the calcaneus bone, is a rare site for tumors, with benign tumors being the most common. The scarcity of studies on tumors in this region complicates diagnosis and may lead to inadequate clinical management. This study presents a case that illustrates the challenge of diagnosing a plantar tumor in the hindfoot and other possible differential diagnoses. The symptoms of both conditions are similar, with pain during physical exertion in the subcalcaneal region, requiring imaging exams and rheumatological marker analysis for exclusion purposes. Treatment for plantar fasciitis consists of conservative therapy, based on the use of anti-inflammatory drugs and physical therapy. For tumors in the hindfoot region, such measures are not effective, with persistent pain being a characteristic feature. In this case, surgical treatment should be considered, and the article discusses the methods for surgical removal of the tumor.